2011
DOI: 10.1073/pnas.1107782108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unnatural alkaloid scaffolds by exploiting plant polyketide synthase

Abstract: HsPKS1 from Huperzia serrata is a type III polyketide synthase (PKS) with remarkable substrate tolerance and catalytic potential. Here we present the synthesis of unnatural unique polyketide-alkaloid hybrid molecules by exploiting the enzyme reaction using precursor-directed and structure-based approaches. HsPKS1 produced novel pyridoisoindole (or benzopyridoisoindole) with the 6.5.6-fused (or 6.6.5.6-fused) ring system by the condensation of 2-carbamoylbenzoyl-CoA (or 3-carbamoyl-2-naphthoyl-CoA), a synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 42 publications
0
41
0
3
Order By: Relevance
“…11A), whereas the S348G mutant takes three units of the extender units, yielding a biologically active alkaloid, 1,3-dihydroxy-5H-dibenzo[b,e]azepine-6,11-dioine (Fig. 11B) (48). An earlier research also reported the biosynthesis of 4-hydroxy-2(1H)-quinolones, a novel alkaloidal scaffold, by the BAS from R. palmatum with N-methylanthraniloyl-CoA and anthraniloyl-CoA as the starter units (49).…”
Section: Biosynthesis Of Novel Molecules By Type III Pkss Through Prementioning
confidence: 99%
“…11A), whereas the S348G mutant takes three units of the extender units, yielding a biologically active alkaloid, 1,3-dihydroxy-5H-dibenzo[b,e]azepine-6,11-dioine (Fig. 11B) (48). An earlier research also reported the biosynthesis of 4-hydroxy-2(1H)-quinolones, a novel alkaloidal scaffold, by the BAS from R. palmatum with N-methylanthraniloyl-CoA and anthraniloyl-CoA as the starter units (49).…”
Section: Biosynthesis Of Novel Molecules By Type III Pkss Through Prementioning
confidence: 99%
“…We selected a type III polyketide synthase HsPKS1 from the plant Huperzia serrata to assemble polyketide backbones using malonyl-CoA extender units. HsPKS1 is able to accept a variety of starter units including aromatic and aliphatic (C 6 -C 10 ) CoA thioesters 29 , suggesting that the recognition of the 5-hexynoyl starter unit would be likely. Two plasmids encoding jamABC and hspks1, with each gene regulated by a T7 promoter, were transformed into the E. coli BAP1 strain 30 yielding the strain XZ1 (Supplementary Fig.…”
Section: Engineered Biosynthesis Of Alkyne-tagged Natural Productsmentioning
confidence: 99%
“…Simultaneous mutation of the neighbouring Phe66 residue to leucine resulted in an OKS double mutant that is capable of synthesizing an unnatural dodecaketide naphthophenone TW95a (70) by the successive decarboxylative condensations of 12 units of malonyl-CoA, making it one of the longest polyketide synthesized by the structurally simple type III PKS (Scheme 24C) [104]. A recently discovered CHS from a primitive club moss Huperzia serrata (HsPKS1) was found to display unusually broad substrate selectivity and produced unnatural polyketide-alkaloid hybrid molecules [105]. Using precursor-directed approaches, HsPKS1 synthesized a novel pyridoisoindole (74) from the condensation of 2-carbamoylbenzoyl-CoA (71), a synthetic nitrogen-containing non-physiological starter, with two units of malonyl-CoA (Scheme 25A).…”
Section: Structure-based Engineering and The Versatility Of Type III mentioning
confidence: 99%
“…The structure-based S348G mutant (corresponding to Ser338 in alfalfa CHS) results in an expansion of the active site cavity which not only extended the polyketide chain length, but also altered the cyclization mechanism to yield a biologically active, ring-expanded dibenzoazepine (75) from the condensation of 2-carbamoylbenzoyl-CoA with three units of malonyl-CoA (Scheme 25B). A recently discovered CHS from a primitive club moss Huperzia serrata (HsPKS1) was found to display unusually broad substrate selectivity and produced unnatural polyketide-alkaloid hybrid molecules [105]. Using precursor-directed approaches, HsPKS1 synthesized a novel pyridoisoindole (74) from the condensation of 2-carbamoylbenzoyl-CoA (71), a synthetic nitrogen-containing nonphysiological starter, with two units of malonyl-CoA (Scheme 25A).…”
Section: Structure-based Engineering and The Versatility Of Type III mentioning
confidence: 99%